Cold-start emissions from petrol and diesel vehicles according to the emissions regulations (from Euro 92 to Euro 2000). (20th February 2004) - Cotte, Helene; Bessagnet, Bertrand; Blondeau, Christian; Mallet-Hubert, Pierre-Yves; Momique, Jean-Claude; Walter, Christian; Boulanger, Laura; Deleger, Didier; Jouvenot, Gilles; Pain, Clarisse
Knowledge of cold-start emissions is one of the major elements in emissions inventories, particularly for urban conditions. Moreover, from January 2000 the new European driving cycle (tests conditions) for vehicle certification (Euro 2000) is modified to properly address this issue (so called "deletion of 40 sec."). In order to characterise both the cold driving distance and the relative emissions levels, measurements on a chassis dynamometer with a dilution tunnel have been carried out on 10 vehicles (five petrol cars, five diesel cars - Euro 92, 96 and 2000). Regulated emissions have been measured second by second over cycles based upon repetition of short elementary units derived from the ECE driving cycle in order to reproduce the same kinematics conditions. The stabilisation of the emissions was used to define the end of the cold period. For petrol powered vehicles, the results show that the length of the cold trip is neither dependant on the type of vehicle nor on the cycle. On average, this distance is less than 1.5 km whatever the pollutant you consider. However, better engine management and improvement of the after treatment system allow a significant decrease of the cold-start emissions between 1992 and 2000 technologies. For diesel powered vehicles, cold-start-emissions (cold engine, water temperature below 70°C) are close to hot emissions. Hence, it is not appropriate to talk about cold-start over-emissions for diesel vehicles. The results have shown a great reduction of all the emissions over the urban driving cycle, from 1992 to 2000 technologies.